PENGARUH HARGA, FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT.BERSIH SEHAT CABANG PURI KENCANA JAKARTA BARAT (STUDI PELANGGAN BERSIH SEHAT PURI KENCANA) - Slamet; Lucy Nancy (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
The purpose of this study was to determine the effect of price, facilities and service quality on customer satisfaction at PT.Bersih Sehat Puri Kencana simultaneously or partially. The number of respondents in this study were 100 people. This research is a descriptive study with a causal associative approach. Sampling using non-probability sampling technique. The data analysis technique uses multiple linear regression analysis accompanied by the F test (simultaneous), t test (partial), and the coefficient of determination (Adjusted R Square) with the help of SPSS 20 software. The results of this study show simultaneously (F test) Price, Facilities and Service quality has a significant and significant effect on customer satisfaction. Partially (t test) shows that price, facilities and service quality, while price and service quality have a significant effect on Purchase Decisions. With a coefficient of determination (Adjusted R Square) of 41%, it means that customer satisfaction cannot be explained by price, facilities and service quality, while 59% of purchasing decisions are influenced by variables not explained in this study.